2004
DOI: 10.1093/molbev/msh150
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogenetic Relationship of Tetrapod, Coelacanth, and Lungfish Revealed by the Sequences of Forty-Four Nuclear Genes

Abstract: The origin of tetrapods is a major outstanding issue in vertebrate phylogeny. Each of the three possible principal hypotheses (coelacanth, lungfish, or neither being the sister group of tetrapods) has found support in different sets of data. In an attempt to resolve the controversy, sequences of 44 nuclear genes encoding amino acid residues at 10,404 positions were obtained and analyzed. However, this large set of sequences did not support conclusively one of the three hypotheses. Apparently, the coelacanth, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 55 publications
2
110
0
Order By: Relevance
“…Lungfishes are believed by many neontologists to be a sister group of amphibians (Forey, 1986); support for this view comes from molecular phylogenetic studies, which show lungfishes to be the closest living relatives of tetrapods (Zardoya et al, 1998;Tohyama et al, 2000;Takezaki et al, 2004;Hallstrom and Janke, 2009;Amemiya et al, 2013). A study by Davidson et al (2003a) on the molecular evolution of vertebrate blood coagulation showed that the blood coagulation network was well established in all the jawed vertebrates and that it evolved before the divergence of teleosts and tetrapods, which occurred more than 430 million years ago.…”
Section: Molecular Characterization Of F2 and Fgg From P Annectensmentioning
confidence: 99%
See 1 more Smart Citation
“…Lungfishes are believed by many neontologists to be a sister group of amphibians (Forey, 1986); support for this view comes from molecular phylogenetic studies, which show lungfishes to be the closest living relatives of tetrapods (Zardoya et al, 1998;Tohyama et al, 2000;Takezaki et al, 2004;Hallstrom and Janke, 2009;Amemiya et al, 2013). A study by Davidson et al (2003a) on the molecular evolution of vertebrate blood coagulation showed that the blood coagulation network was well established in all the jawed vertebrates and that it evolved before the divergence of teleosts and tetrapods, which occurred more than 430 million years ago.…”
Section: Molecular Characterization Of F2 and Fgg From P Annectensmentioning
confidence: 99%
“…Many neontologists consider lungfishes as a sister group of amphibians (Forey, 1986), but this view is opposed by paleontologists (Marshall and Schultze, 1992), who usually support a single origin of tetrapods, starting from the Rhipidistia, which is an extinct group of lobe-finned bony fishes. In contrast, molecular phylogenetic studies favour the lungfishes as the closest living relatives of tetrapods (Zardoya et al, 1998;Tohyama et al, 2000;Takezaki et al, 2004;Hallstrom and Janke, 2009;Amemiya et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…2), in which lungfishes are also included. Indeed, molecular phylogenetic studies clearly indicate that coelacanths and lungfishes are more closely related to tetrapods than to teleost fishes (e.g., Zardoya and Meyer 1996), whereas the branching order of coelacanths, lungfishes, and tetrapods is still controversial (Takezaki et al 2004). The karyotype of L. chalumnae, which was reported to be 48 chromosomes including microchromosomes, is similar to that of frogs and other species such as turtles or birds, further supporting the phylogenetic closeness of the coelacanth with tetrapods (Bogart et al 1994).…”
mentioning
confidence: 99%
“…they do not place coelacanth sequences on short branches nor do they detect low substitution rates [24,[27][28][29][30][31]. The clearest example, which involves the largest number of genes, is a phylogeny based study of forty-four nuclear genes that does not show a dramatic decrease, if any, in the rate of molecular evolution in the coelacanth lineage [32]. What we know about the biology of coelacanths does not suggest any obvious reason why the coelacanth genome should be evolving particularly slowly.…”
Section: Low Molecular Diversity and Low Geographic Differentiation Imentioning
confidence: 96%